2021
DOI: 10.1590/0103-6440202103951
|View full text |Cite
|
Sign up to set email alerts
|

The influence of roughness on the resistance to impact of different CAD/CAM dental ceramics

Abstract: This study aimed to investigate the effect of surface roughness (polished vs. CAD/CAM milling simulation) on impact strength of five dental ceramics for manufacturing CAD/CAM monolithic restorations. Specimens of five ceramics (FC- feldspathic glass-ceramic; PICN- polymer-infiltrated ceramic-network; ZLS- zirconia-reinforced lithium silicate glass-ceramic; LD- lithium disilicate glass-ceramic; YZ- yttria-stabilized tetragonal zirconia polycrystal ceramic) to be tested under impact (15×10×2mm3; n= 15) were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The roughness data from this study showed that smoothness was significantly greater for polished than for glazed ceramics in all three cases (before and after immersion in solutions), although in another study, polishing was found to produce rough surfaces while glazing produced a smoother surface 10 . The difference may be attributed to different specimen preparation techniques, polishing techniques 11 , materials 12 or Ra machine used 13 . The surface roughness of polished specimens did not differ after immersion in coffee or water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The roughness data from this study showed that smoothness was significantly greater for polished than for glazed ceramics in all three cases (before and after immersion in solutions), although in another study, polishing was found to produce rough surfaces while glazing produced a smoother surface 10 . The difference may be attributed to different specimen preparation techniques, polishing techniques 11 , materials 12 or Ra machine used 13 . The surface roughness of polished specimens did not differ after immersion in coffee or water.…”
Section: Discussionmentioning
confidence: 99%
“…smoother surface 10 . The difference may be attributed to different specimen preparation techniques, polishing techniques 11 , materials 12 or Ra machine used 13 . The surface roughness of polished specimens did not differ after immersion in coffee or water.…”
Section: Discussionmentioning
confidence: 99%